A mitochondria-targeting dinuclear Ir–Ru complex as a synergistic photoactivated chemotherapy and photodynamic therapy agent against cisplatin-resistant tumour cells. Issue 83 (2nd October 2019) - Zhang, Cheng; Guan, Ruilin; Liao, Xinxing; Ouyang, Cheng; Rees, Thomas W.; Liu, Jiangping; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : A mitochondria-targeting hetero-binuclear complex (Ir–Ru ) was developed for the synergistic photoactivated chemotherapy and photodynamic therapy of cisplatin-resistant tumour cells. Abstract : A mitochondria-targeting hetero-binuclear Ir(iii )–Ru(ii ) complex was developed as a photoactivated chemotherapy (PACT) and photodynamic therapy (PDT) bifunctional agent to achieve a synergistic effective therapeutic outcome for the therapy of cisplatin-resistant tumour cells.